2011
DOI: 10.3109/0886022x.2011.574768
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Reporting Estimated Glomerular Filtration Rate

Abstract: The 'Kidney Disease Outcomes Quality Initiative' guidelines recommend laboratory reporting of a calculated estimated glomerular filtration rate (eGFR). The United Kingdom and several states already mandate reporting eGFR for every laboratory serum creatinine (sCr) measurement. In our study, we evaluated the impact of reporting eGFR on the management of hospitalized patients. We reviewed the medical records for 2000 patients, 1000 pre-and 1000 post-reporting eGFR. We excluded patients with previous diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These guidelines recommend the use of estimated glomerular filtration rate (eGFR) equations to estimate a patient’s renal function. At the present time several articles have been published about, evidencing the impact of these guidelines in clinical practices daily (2325). When considering that accurate serum creatinine determination is necessary for deriving the above eGRF equations, changes of serum vacuum tubes principally from Tube III to Tube IV (with clinically significant difference) can induce diagnostic errors regarding patient real conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines recommend the use of estimated glomerular filtration rate (eGFR) equations to estimate a patient’s renal function. At the present time several articles have been published about, evidencing the impact of these guidelines in clinical practices daily (2325). When considering that accurate serum creatinine determination is necessary for deriving the above eGRF equations, changes of serum vacuum tubes principally from Tube III to Tube IV (with clinically significant difference) can induce diagnostic errors regarding patient real conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, non-compliance with dosing guidelines in hospitalized patients with chronic kidney disease ranges from 19% to 67% [69]. Evidence suggests that reporting estimated glomerular filtration rate (eGFR) may not significantly change prescription habits for nephrotoxic medications, including antibiotics [70,71]. Recently, Joosten et al [60] showed that introducing automatic renal function alerts in the ambulatory care setting, with the involvement of both general practitioners and community pharmacists, was able to reveal that a considerable proportion of the population is at risk for adverse drug events due to impaired renal function.…”
Section: Setting and Intervention Evidencementioning
confidence: 99%